The philosophy of Gandhi : a study of his basic ideas - Richards, Glyn. (Richmond, Surrey : Curzon Press, 1991)
Seeks to give a coherent account of Gandhi's basic ideas. The book begins with an analysis of his central concept of "truth", and proceeds to show how a "prima facie" abstract concept so determines his way of life that it becomes the raison d'etre of his existence.
Preliminaries; CONTENTS; PREFACE; I THE CONCEPT OF TRUTH; II TRUTH AND RELIGION; III TRUTH AND AHIMS; IV SATY GRAHA; V SARVODAYA; VI TRUTH AND SOCIETY; VII TRUTH AND SOCIETY EDUCATION; VIII TRUTH AND ECONOMICS; IX TRUTH AND POLITICS; X CONCLUSION; GLOSSARY; BIBLIOGRAPHY; INDEX.
Includes bibliographical references (pages 169-172) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Gandhi, -- Mahatma, -- 1869-1948.; Gandhi, -- Mahatma, -- 1869-1948; PHILOSOPHY -- Hindu